Conflict in the boardroom: perceptions of board members in the Nordic Region. Issue 2 (3rd April 2021) - Pastra, Aspasia; Koufopoulos, Dimitrios N.; Samac, Nikola; Johansson, Tafsir
Abstract: The purpose of this study is to explore the relationship between conflict in the boardroom and board performance in the Nordic Region. Embracing the information-processing perspective, we conceptualize board of directors as information processing systems that process large amounts of data and any type of conflict could affect their performance. Using primary data from 184 member of different boards, we conducted exploratory factor analyses of the used scales in order to confirm their proposed factor structure. After confirming their validity and reliability, hierarchical multiple regressions were applied. Results indicate that: (1) Relationship conflict has a negative effect on the performance of the board in providing strategic leadership and readiness; and (2) Process conflict negatively predicts strategic leadership. The above findings advance theoretical understanding of conflict in the boardroom and underline the need for a clear distinction between relationship conflict and process conflict since the two exist at different levels of the 'conflict' structure and instigated by different factors hinting different effects on board performance. Our study has several contributions to managerial practice, such as that personal friction among directors at the board meetings impacts both the strategic leadership of the board and its readiness in anticipating threats. In addition, process conflict in the boardroom may lead to misjudgments about shaping and implementing organizational strategy.